Evaluation of mandibular length in subjects with Class I and Class II skeletal patterns using the cervical vertebrae maturation - Rodrigo Generoso; Elaine Cristina Sadoco; Mônica Costa Armond; Gustavo Hauber Gameiro (Sociedade Brasileira de Pesquisa Odontológica, 2010)
The aim of this study was to compare the mandibular size in boys and girls with Class I and Class II skeletal patterns, taking into consideration the bone maturation stage, as defined by the cervical vertebrae maturation. One hundred and sixty cephalometric radiographs were obtained from subjects (aged between 7 and 12 years) with Class I or Class II skeletal patterns, according to the ANB angle and WITS appraisal. The Class I sample consisted of 80 subjects (40 boys, 40 girls). The Class II sample also consisted of 80 subjects (40 boys, 40 girls). On a cross-sectional basis, mandibular length (Co-Gn) was compared between groups and genders. The between-stages changes were also evaluated, with the cervical vertebrae analysis used for establishing the bone maturation stages at CS2, CS3, CS4 and CS5. The results were statistically analyzed by the Kruskal-Wallis test. The mandibular length differed between skeletal patterns only at the earlier stages of development. In the Class I pattern, the mandibular lengths of boys were greater than those of girls at stages CS2, CS4 and CS5, whereas in the Class II pattern, the mandibular lengths of boys were greater than those of girls at stages CS2, CS3 and CS4. The present results indicate a sexual dimorphism in the mandibular length at almost all stages of bone maturation, in exception of the CS5 stage in Class II.